The sneeze reflex in physiological and pathological states: a mini review - Rui, Yang; Xin, Tianyuan; Chen, Yu; Xiang, Beiyi; Chen, Changwen; Dong, Rong; Chen, Zhe (Frontiers in Neuroscience, 2025)
The sneeze reflex serves as a protective response of the human body to environmental stimuli, with its regulatory mechanism largely depending on a complex nervous system. Current research indicates that the sneeze reflex can be triggered by both internal and external stimuli, including light and temperature. The composition of its reflex arc involves the coordinated action of multiple neural structures. Recent in-depth studies on the mechanism of the sneeze reflex have revealed a growing association between this reflex and various diseases, such as allergic rhinitis and infectious diseases. However, existing research primarily focuses on elucidating the neurophysiological basis of the sneeze reflex and its related neural pathways. The manifestations and mechanisms of the sneeze reflex under different pathological states remain underexplored, thereby limiting the potential application of the sneeze reflex in clinical diagnosis and treatment. This review aims to discuss the physiological mechanisms and pathological manifestations associated with the sneeze reflex.